The Role of Technology in Operational Management Process Selection - Hasdiansa, Ilma Wulansari (PT. Maju Malaqbi Makkarana, 2024)
The selection of operational management processes is significantly influenced by technology, which can enhance the efficiency and effectiveness of company operations. The application of information technology enables organizations to manage equipment, human resources, and production processes in a more efficient and effective manner. In the selection of operational management processes, information technology plays a pivotal role in identifying and selecting production processes that align with the needs of the organization. Furthermore, information technology facilitates the implementation of effective human resource management systems. This paper examines the role of technology in operational management process selection and the impact of information technology on organizational operations.